Analysis of Trade, Unemployment, Government Contribution to Poverty in Three Poorest Countries in the World - Adinda Nurul Huda, Stevani; Handayani, Nicky; Juwita, Ratih (International Journal of Psychosocial Rehabilitation, 2020)
The aim of this study is to determine the factors that affect poverty in the world such as trade, unemployment rate, government in three countries with highest poverty rate in the world (Central Africa, Congo, and Malawi). This study uses secondary data, which is accessed through https://id.tradingeconomics.com in the period 2012-2016. The analytical tool used in this study using multiple linear regression (using SPSS) and to analyze the simultaneous influence of the variables used (F Test) and partially for research variable (t test). The results of this study there is a significant influence of the unemployment variable on poverty of 0.000 under 5%, while the results are different there is no significant influence of government variables and trade against poverty respectively by 30% and 6.7% well above the profitability of 5%. The test results simultaneously from three independent variables are F-Stat equal to 8.691 with probability 0.003, because the probability is much smaller than 0.05 then the regression model can be used to predict trade, unemployment rate, and governance collectively affect poverty.